PERANCANGAN SISTEM KONSULTASI KESEHATAN ONLINE BERBASIS WEBSITE GUNA MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PELAYANAN KESEHATAN PADA UPTD PUSKESMAS TIGA BALATA TAHUN 2025 - Wahab, Bachtiyar - (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
Digital transformation in the health sector has encouraged the adoption of technology-based services to improve the efficiency and effectiveness of healthcare delivery, particularly in primary care facilities such as community health centers (Puskesmas). This study aims to design a web-based online health consultation system for UPTD Puskesmas Tiga Balata to provide faster, more efficient, and accessible services. A qualitative research method with an action research approach was employed, utilizing the System Development Life Cycle (SDLC) for system development. The design process included needs analysis, system design using flowcharts, context diagrams, data flow diagrams, and entity relationship diagrams, followed by implementation using PHP and MySQL database. The results demonstrated that the system successfully provided key features such as user login, doctor listings, consultation media, health news, and an online chat system between patients and healthcare workers. System testing was conducted using black box testing, confirming that the application met the defined requirements. This web-based system is expected to be a digital solution that enhances healthcare services, especially in remote areas, and it is recommended for further development into a mobile version to improve accessibility.